Nurses’ Lived Experiences Following End-of-Life Care: A Hermeneutic Study from a North-Central State, Nigeria - Oyediran, Olufemi Oyebanji; Ishola, Kofoworola Ebunoluwa; Ayandiran, Emmanuel Olufemi; Olatubi, Idowu Matthew (Nurse Media Journal of Nursing, 2025)
Background: Death is a common occurrence in nursing practice, and nurses are expected to provide professional and sensitive care to families, which can be psychologically demanding. However, there is a paucity of studies describing the experiences of nurses dealing with pediatric end-of-life (EOL) care and death.Purpose: This study explored nurses’ lived experiences following EOL care among pediatric nurses working in two selected hospitals in Nigeria.Methods: A hermeneutic qualitative design was adopted to describe and interpret participants’ experiences. Twenty-one nurses were purposively selected from pediatric wards. Data were collected through semi-structured, in-depth interviews and analyzed using ATLAS.ti with thematic analysis.Results: Five themes emerged: (1) EOL care training during nursing education, (2) experiences of EOL care as a practicing nurse, (3) perceived contributing factors to child death, (4) nurses’ roles in supporting families after child loss, and (5) coping strategies for managing grief after pediatric patient death. The findings revealed that nurses are affected by the death of a child regardless of years of experience. Limited knowledge of EOL care negatively influenced their coping abilities. Nurses considered open grieving unprofessional, with the primary coping strategy being increased commitment to work.Conclusion: The study concluded that years of work experience do not significantly influence nurses’ lived experiences of pediatric patient death. Limited knowledge of EOL care strongly shapes their perspectives on death, dying, and grieving. Grieving is perceived as unprofessional, while dedication to work serves as the preferred coping mechanism. Mandatory training on EOL nursing care and the provision of institutional guidelines are recommended.